Cardiovascular Disease Parameters in Periodontitis - Monteiro, Andrea M.; Jardini, Maria Aparecida Neves [UNESP]; Alves, Sarah; Giarnpaoli, Viviana; Aubin, Elisete C. Q.; Figueiredo Neto, Antonio M.; Gidlund, Magnus (Amer Acad Periodontology, 2009)
Background: Recently, there has been an increasing in the impact of oral health on atherosclerosis and subsequent cardiovascular disease. The aim of this study is to investigate the association between chronic periodontitis and cardiovascular risk markers.Methods: Forty patients with periodontitis and 40 healthy gender-, body mass index-, and age-matched individuals were compared by measuring total cholesterol, high-density lipoprotein, low-density lipoprotein, triglycerides, levels of cytokines, antibodies against oxidized low-density lipoprotein, thiobarbituric acid reactive substances, total and differential white blood cell counts, and the non-linear index of refraction.Results: The levels of triglycerides and high-density lipoprotein in periodontitis patients were significantly higher and lower, respectively (P=0.002 and P=0.0126), compared to controls. Total cholesterol, low-density lipoprotein, and lipid peroxide levels were the same in both groups (P = 0.2943, P = 0.1284, and P = 0.067, respectively). Interleukin (IL)-6 and -8, antibodies against oxidized low-density lipoprotein, and leukocyte and neutrophil counts were significantly higher in periodontitis patients (P<0.05). The value of the non-linear index of refraction of low-density lipoprotein solutions was higher in the controls (P = 0.015) compared to individuals with periodontitis.Conclusion: Our results confirmed and further strengthened the suggested association between coronary artery disease and periodontitis. J Periodontol 2009;80:378-388.
Keywords: Antibodies; atherosclerosis; cardiovascular; oxLDL; periodontitis; risk factors